Profiling of dengue vectors breeding habitat at urban residential areas in Shah Alam, Malaysia - Faiz Madzlan,; Nazri Che Dom,; Nurmahirah Zakaria,; Siti Nur Anis Hasnan,; Chua, Say Tiong; Siti Nazrina Camalxaman, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
Dengue fever is an urban vector-borne disease transmitted by Aedes aegypti and Aedes albopictus. Both species lay their eggs in favourable breeding containers either in natural or artificial containers. Thus, an understanding of Aedes species habitat characteristics is important in combating dengue fever outbreaks. A minimum of 100 houses were inspected the peridomestic area for Aedes species in central zone of Shah Alam. Larval surveillance and water analysis were conducted to determine water breeding characteristic while larval species identification was conducted used to determine dominant species in Shah Alam. Aedes immatures were identified by using standard entomological procedures. Aedes albopictus easily found throughout the localities while plastic container become most preferences breeding container and paint cans were the favourable breeding container. pH and sodium are considered as the water parameters that enhanced the development of Aedes larvae with p-value of 0.001 and 0.000 respectively. By identifying the key of habitat characteristic of Aedes species through larval surveillance, the vector control can be implemented efficiently throughout the central zone of Shah Alam.